(untitled) (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACT— The future of communication is safe and reliable. The functionality of futuristic apps depends on a few key features. This research classifies these application needs into two key groups to show how blockchain and 6G may impact future communication systems. Data rates, latency, dependability, and the ability to handle a huge connection capacity are the primary concerns of Requirement Group I (RG-I). Data integrity, non-repudiability, and auditability are the main concerns of Requirement Group II (RG-II). By decentralizing and making resource sharing easier, blockchain and 6G technology would help achieve RG-I’s goals and reduce wasteful overuse of assets. The RG-II requirements can be easily met by 6G applications using appropriate blockchain and consensus technology. This research suggests that in the future, dependable and broad connectivity can be achieved through the integration of blockchain technology and 6G.